The relationship between income inequality, poverty, and globalization - Almas Heshmati (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper introduces two composite indices of globalization. The first is based on the Kearney/Foreign Policy magazine and the second is obtained from principal component analysis. They indicate the level of globalization and show how globalization has developed over time for different countries. The indices are composed of four components: economic integration, personal contact, technology and political engagement, each generated from a number of indicators. A breakdown of the index into major components provides possibilities to identify the sources of globalization at the country level and associate it with economic policy measures. The empirical results show that a low rank in the globalization process is due, in addition to involvement in conflicts, to economic and technology factors with limited possibility for the developing countries to affect. The high ranked developed countries share similar patterns in distribution of various components. The indices were also used in a regression analysis to study the causal relationships between income inequality, poverty and globalization. The results show evidence of a weak and negative relationship between globalization and income inequality and poverty. – globalization ; income inequality ; poverty ; indices ; principal component
Keywords: C23; D63; F15; O57; 330; Einkommensverteilung; Armut; Globalisierung; Wirtschaftsindikator; Schätzung; Welt; Entwicklungsländer